Constitutive Overexpression of RAM1 Leads to an Increase in Arbuscule Density in Brachypodium distachyon. Issue 3 (1st September 2020) - Müller, Lena M.; Campos-Soriano, Lidia; Levesque-Tremblay, Veronique; Bravo, Armando; Daniels, Dierdra A.; Pathak, Sunita; Park, Hee-Jin; Harrison, Maria J.
Abstract : In Brachypodium distachyon, the GRAS family transcriptional regulator RAM1 is partially required for arbuscule development and, when overexpressed, increases arbuscule density. Abstract: Arbuscular mycorrhizal (AM) symbiosis is a mutually beneficial association of plants and fungi of the subphylum Glomeromycotina. Endosymbiotic AM fungi colonize the inner cortical cells of the roots, where they form branched hyphae called arbuscules that function in nutrient exchange with the plant. To support arbuscule development and subsequent bidirectional nutrient exchange, the root cortical cells undergo substantial transcriptional reprogramming. REDUCED ARBUSCULAR MYCORRHIZA1 ( RAM1 ), previously studied in several dicot plant species, is a major regulator of this cortical cell transcriptional program. Here, we generated ram1 mutants and RAM1 overexpressors in a monocot, Brachypodium distachyon. The AM phenotypes of two ram1 line s revealed that RAM1 is only partly required to enable arbuscule development in B. distachyon . Transgenic lines constitutively overexpressing BdRAM1 showed constitutive expression of AM-inducible genes even in the shoots. Following inoculation with AM fungi, BdRAM1 -overexpressing plants showed higher arbuscule densities relative to controls, indicating the potential to manipulate the relative proportion of symbiotic interfaces via modulation of RAM1 . However, the overexpressors also show altered expression of hormone biosynthesis genes and aberrant growth patterns, including stunted bushy shoots and poor seed set. While these phenotypes possibly provide additional clues about the scope of influence of BdRAM1, they also indicate that directed approaches to increase the density of symbiotic interfaces will require a more focused, potentially cell type specific manipulation of transcription factor gene expression.